If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 70 + x Solving 6x = 70 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 6x + -1x = 70 + x + -1x Combine like terms: 6x + -1x = 5x 5x = 70 + x + -1x Combine like terms: x + -1x = 0 5x = 70 + 0 5x = 70 Divide each side by '5'. x = 14 Simplifying x = 14
| x^3+3=5x | | 15=6-2x-x | | -15=m+-15 | | 4ab-2a-2b+1= | | -7=-9+x/7 | | 4a+20=48 | | -44=4v-8 | | x^3+3=5 | | 1=v+(-2) | | 16x-9x=42 | | 3u-7=-22 | | 8+2w=-6 | | 4x+33=8x-3 | | 16=-3y-5y | | 1x^2+5x+6=3 | | (x^4)+4=0 | | x=-10+2y | | 6x+17=-24-6x | | 3(2x+5)-x=6x+6 | | f(x)=2x^2+8x-12 | | 3(2x+5)-x=5x+6 | | x^2-29x+99=0 | | 3(2x+5)-x=5x+7 | | 2y-15=y-6 | | 3(2x+5)-x=3x+5 | | 3(2x+5)-x=5x+3 | | 5x+3y=1000 | | 3(2x+5)-x=5x+5 | | 2x+7+2x+7+4x+3= | | (9x-5)-(2x-8)= | | 14+3t=8t-3(t-4) | | 30+4x=90 |